Empowering Problem-Solving Skills Through RICOSRE Learning Model - Tesa Manisa; Susriyati Mahanal; Fatchur Rohman (Universitas Negeri Malang, 2020)
Abstract: This study aims to determine the influence of RICOSRE (Reading, Identfying problem, Constructing Solution, Solving Problem, Reviewing Problem Solving, and Extending Problem Solving) learning model toward X grade students' Biology problem solving in two high school. This type of research is quasi experiment research. The sample used is the students in three classes each schools that is determined by cluster random sampling. The research data collected by pretest and posttest score. Data analysis using two way ancova and then continued with LSD 5%. The research result indicate RICOSRE learning model significantly influenced the X grade students' problem solving with a corrected average of problem solving achievement is 87,83%. Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran RICOSRE (Reading, Identfying problem, Constructing Solution, Solving Problem,Reviewing Problem Solving, and Extending Problem Solving) terhadap keterampilan memecahkan masalah siswa Kelas X MIPA di dua SMA. Jenis penelitian adalah penelitian kuasi eksperimen. Sampel yang digunakan ialah siswa pada masing-masing tiga kelas di setiap sekolah yang ditentukan secara cluster random sampling. Pengumpulan data penelitian menggunakan pretest dan posttest. Analisis data dilakukan dengan uji two way ancova kemudian dilanjutkan dengan uji lanjut LSD 5%. Hasil penelitian menunjukkan terdapat pengaruh model pembelajaran RICOSRE terhadap keterampilan memecah-kan masalah siswa. Siswa mengalami peningkatan keterampilan memecahkan masalah sebesar 87,83%.